CSIG-12. BXQ-350 INDUCES MITOPHAGY IN GBM CELLS LEADING TO CELL DEATH. (14th November 2022) - Wilkins, Nikhil; Furnish, Robin; Stephens, Tim
Abstract: BACKGROUND: Mitophagy is an autophagic phenomenon where defective mitochondria are selectively degraded. When mitochondria need recycling, the cell upregulates the production of the lipid C-18 ceramide on the mitochondria and lipoprotein LC3B-II on the lysosome, which transitions to an autophagolysosome. This creates a signal causing the degradation of mitochondria. Here we show that BXQ-350, a novel protein-lipid small molecule consisting of the ceramide creating protein Saposin C and the lipid Dioleoyl Phosphatidylserine (DOPS), induces glioblastoma cells into performing mitophagy. Increased production of mitophagy associated proteins, C-18, and LC3B-II leads to the degradation of healthy mitochondria followed by cell death. METHODS: The GBM cell lines, Gli36 and U87 cells, were used to determine if increased mitophagy was occurring in response to BXQ-350 treatment. Protein abundance was measured using SILAC proteomics. Ceramide levels were analyzed using LC/MS-MS. Western Blot analysis was used to measure differences in LC3B-II levels. Mitophagy was measured using Mtphagy Dye from Dojindo and the BioTek Cytation 5 microscope. RESULTS: Proteomics showed cells treated with BXQ-350 had an increase in proteins associated with overexpression of C-18 ceramide or autophagolysosome maturation. Western blots analysis showed a marked increase in LC3B-II in BXQ-350 treated cells. Furthermore, cells treated with BXQ-350 had increased levels of C-18 ceramide. The Mtphagy dye showed that as BXQ-350 concentrations increased, the percentage of cells positive for Mitophagy increased. To determine if mitophagy occurs in association with BXQ-350 cytotoxicity, medias with varying BXQ-350 cytotoxicity were used. The Mtphagy dye showed cytotoxic BXQ-350 medias increased levels of mitophagy, while noncytotoxic medias display no increase in mitophagy. CONCLUSION: BXQ-350 causes the increase of mitophagy signaling proteins, C-18 ceramide and LC3B-II production, resulting in the formation of autophagolysosomes which track towards the mitochondria initiating mitophagy. This leads to aberrant mitophagy where cells degrade healthy mitochondria leading to mitophagic cell death.